Congenital Lung Malformations: Clinical and Functional Respiratory Outcomes after Surgery - Andrea Farolfi; Michele Ghezzi; Valeria Calcaterra; Giovanna Riccipetitoni; Gloria Pelizzo; Sara Costanzo; Emma Longoni; Annalisa De Silvestri; Nicolò Garancini; Salvatore Zirpoli; Gianvincenzo Zuccotti (MDPI AG, 2022)
Congenital lung malformations (CLMs) involve anomalies of the lungs and respiratory tree such as congenital pulmonary airway malformation (CPAM), pulmonary sequestration (PS), bronchogenic cysts, congenital lobar emphysema, and bronchial atresia (BA). Although symptomatic lesions require surgical resection, the appropriateness of surgery for patients with asymptomatic malformations is a matter of ongoing debate. Limited data are available concerning the long-term follow-up of affected subjects. In this study, we sought to evaluate the long-term clinical and functional respiratory outcomes in children with CLMs who underwent surgical resection. We carried out a retrospective analysis of 77 children with CLMs who underwent pulmonary resection with at least one year of follow-up. The most common diagnoses were CPAM (50.65%), hybrid lesions (25.97%), lobar emphysema (11.69%), and PS (5.19%). The most common surgical approaches were lobectomy (61.3%), segmentectomy (10.7%), and pneumonectomy (5.3%). Acute post-surgery complications occurred in 31.2% of children. In addition, 73.7% experienced long-term complications, and we found no correlation between the presence of these complications and the sex of the patients, their age at time of surgery, the type of surgery undergone, the presence of symptoms prior to intervention, or acute complications after surgery. Pulmonary function tests revealed FEV1 Z-scores of <−2 SDs in 16 patients, and we found a significant correlation between pneumonectomy and the development of lung function deficit (p = 0.031). In conclusion, clinical and functional respiratory complications may occur in children with CLMs who undergo surgical resection. Long-term monitoring is needed to improve the management of asymptomatic patients.